Direct lateral approach for hemiarthroplasty: a case series - Chanda, Ashoke K.; Mandal, Raju; Dasgupta, Sudipta; Biswas, Kousik; Dalal, Rayan; Mudi, Himangshu (International Journal of Research in Orthopaedics, 2024)
Worldwide, hip fractures are a public health concern. The primary course of treatment for displaced femoral neck fractures is still surgery. Even now, hemiarthroplasty remains a highly preferred surgical procedure. The most popular methods for gaining access to the hip joint are the direct lateral and posterior approaches. Aim of this series is to research the short-term functional results, risks, and disadvantages of the direct lateral approach to the hip. Patients with traumatic neck of femur fracture coming to the Department of Orthopaedics, Calcutta National Medical College and Hospital and was elected for bipolar hemiarthroplasty as treatment option. Among the 12 cases 9 were males and 3 were females. The value of z is 2.4495. The value of p is 0.01428. The result is significant at p<0.05. Garden’s classification - there were 2 cases of type 3 garden and 10 cases of type 4 garden fractures. The value of z is 3.266. The value of p is 0.00108. The result is significant at p<0.05. Though there is a chance of iatrogenic gluteal nerve and vascular injury -which we did not encounter in our case - the direct lateral approach exposes the hip joint to a sufficient but limited degree. However, the risk of post-operative hip dislocation is minimal because the rotator cuff of the hip joint is preserved; none of the 12 cases that were chosen had this condition.